CD19 chimeric antigen receptor T-cell therapy following autologous stem cell transplantation against relapsed or refractory Burkitt lymphoma/leukemia: A case report and literature review - Ye, Mingyu; Gao, Lei; Wang, Tao; Yu, Jiechen; Gui, Jiaping; Yang, Jianmin (Frontiers in Oncology, 2022)
Burkitt lymphoma or leukemia (BL) is a highly aggressive non-Hodgkin lymphoma. Older age (over 60 years old) and the presence of high-risk factors (such as abdominal mass, high levels of the serum lactic dehydrogenase, Ann Arbor stage II-IV and so on) usually predict a poorer outcome. Chimeric antigen receptor T cells (CART) have achieved remarkable success in the treatment of B-cell leukemia and lymphoma. Here, for the first time, we report a 61-year-old, high-risk BL patient with autologous stem cell transplantation (ASCT) bridging therapy prior to CART as consolidation therapy. Our findings demonstrate that the combination of ASCT and CART for BL is safe and feasible.